789 Impact of Open Ductus Arteriosus on Cerebral Oxygenation During the First Day of Life. (October 2012) - Binder, C; Urlesberger, B; Einspieler, C; Ziehenberger, E; Müller, W; Pichler, G
Abstract : Background: In neonates the ductus arteriosus (DA) plays an important role in hemodynamics and oxygenation. Aim of this study was to analyse influence of an open DA on cerebral tissue oxygenation (crSO2 ) during the first day of life. Methods: In this prospective observational study near-infrared-spectroscopy (NIRS) measurements were performed on the right forehead during the first 24 hours of life in preterm and term infants. Cardiac ultrasound was performed immediately after beginning and after cessation of NIRS measurements. Based on the second ultrasound infants were divided into "open DA" and "closed DA" group. Diameter and DA-ratio (time left to right/total shunt time) were assessed in case of open DA. Results: Altogether 28 neonates with gestational age of 35±3 weeks and birth weight of 2457±929g were included. Cardiac ultrasounds were performed at 5±3 and 24±5 hours after birth. All infants had an open DA on the first ultrasound without significant difference between the two groups concerning ductal diameter and DA-ratio. 17 neonates had a closed DA and 11 an open DA on the second ultrasound. Groups did not differ in demographic data. crSO2 of closed DA group was significantly higher from 4 to 8 and 10 to 24 hours after birth. Mean crSO2 of the 24 hours was 80% in closed DA and 65% in open DA group. Conclusion: Infants with a closed DA at the end of the first day of life have significantly higher crSO2 during the first 24 hours of life than infants with an open DA.